Epidemiology of malignant neoplasms in child population of Chuvash Republic for the period 1994–2008 - G. P. Pavlova; A. G. Rumyantsev; N. V. Suslonova (Онкогематология)
Aim of this study was to investigate the incidence of malignant neoplasms (MN) in pediatric population (0–17 years) in the Chuvash Republic for the 15-year period (1994–2008). For study period total of 499 MN cases have been reported with an average of 33.3 ± 1.8 cases per year. The incidence rate of MN in children and adolescents was 10.1 ± 0.4 per 100.000. Distinct tendency to a change in the MN incidence rate has not been fo und, a regression analysis line is almost horizontal.